Hormesis as a Pro-Healthy Aging Intervention in Human Beings? - Francine Z. Marques; M. Andrea Markus; Brian J. Morris (SAGE Publishing, 2010)
Hormesis is a phenomenon in which adaptive responses to low doses of otherwise harmful factors (also called mild stressors) make cells and organisms more robust. Aging is a complex and poorly understood process. This review explores the positive effects of hormesis on aging in animal models and human cell cultures, and discusses whether it might apply to humans. As an example, repeated mild heat stress confers anti-aging benefits to normal human cells in culture. Calorie restriction and xenohormetic compounds such as resveratrol, in large part via activation of sirtuins, decrease risk of common age-related conditions, such as cancer, cardiovascular disease, type 2 diabetes, and neurological diseases, so lengthening lifespan. Mild stressors and xenohormetic dietary components have diverse molecular targets and affect many pathways. Despite experimental advances in aging research, findings in humans are still quite limited. Moderate-intensity exercise, weight management and healthy diet ameliorate diseases of aging to increase lifespan and this could involve hormesis.